A systematic review on caregiver's burden among caregivers of dementia patients in Malaysia - Mohd Razi, Nuurain Amirah; Minhat, Halimatus Sakdiah; Mohd. Zulkefli, Nor Afiah; Mohd. Zulkefli, Nor Afiah; Ahmad, Norliza; Tengku Mohd, Tengku Amatullah Madeehah; Jaafar, Hafiz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2023)
Introduction: Increasing prevalence of dementia and the associated caregiving burden are expected due to longer life expectancy. This review aimed to critically assess dementia-driven caregiving burden and the associated factors in Malaysia. Methods: A systematic search using several combinations of keywords was conducted in Ovid Med- line, PubMed, Science Direct, ProQuest, and Ebscohost databases. The primary outcome was the score or level of caregiver burden, while the secondary outcome was the factors associated with such burden. The quality of the individual articles was assessed using the Newcastle“Ottawa Scale and the Joanna Briggs Institute checklist. Results: The systematic search resulted in seven studies being reviewed, consisting of six cross-sectional studies and one quasi-experimental study. Using the Zarit Burden Interview, two studies reported moderate caregiver burden with mean scores of 35.4 (15.08) and 46.0 (17.0). High levels of burden or strain were reported using the Caregiver Strain Index in other studies. The three main associated factors with burden identified in these studies were the presence of behavioural and psychological symptoms of dementia (BPSD), higher education level, and lack of social support. Conclusion: Moderate to severe caregiving burden level were found to be experienced by dementia caregivers in this country. High education, lack of support, as well as taking care of patient with BPSD being the most prominent factors associated with burden. Therefore, burden should be regularly assessed among the dementia caregivers especially among those with lack of social support and manage family members with BPSD, as to prevent adverse outcome from dementia caregiving.